Cystic Fibrosis-Related Diabetes in Adults: Where Can We Go From Here? (The Review of Diabetic Studies, 2023)
Cystic fibrosis (CF), a dysfunction of the exocrine glands, is one of the most frequently diagnosed genetic diseases. It is characterized by chronic pulmonary disease and pancreatic deficiency. Cystic fibrosis-related diabetes (CFRD) is a complication of CF and develops from impaired glucose tolerance via postprandial hyperglycemia with fasting normoglycemia to full-blown diabetes with fasting and postprandial hyperglycemia. CFRD is related to decreased life expectancy, most notably in female patients, as well as to decreased pulmonary function and body weight reduction, which can be improved with adequate insulin therapy. Insulin therapy is accepted in full-blown diabetes but the treatment required by lesser degrees of abnormal glucose metabolism is unknown and needs to be clarified. Chronic organ complications of diabetes are seen only in full-blown diabetes with a particular tendency to affect the autonomous nervous system. Continuous glucose measurement techniques have opened new fields of investigation, particularly in relation to CF-related complications. Insulin therapy needs to be intensified and insulin pump therapy should receive more attention. While improvements in therapy, including lung transplantation, have resulted in increased life expectancies, other issues, such as fertility problems and pregnancy, have raised new questions. All of these need to be addressed to find new treatment options for CFRD patients. In this article we aim to illustrate how these new questions in the treatment of adult patients with CFRD could be answered.